Characterization of the gene encoding the polymorphic immunodominant molecule, a neutralizing antigen of Theileria parva - Toye, Philip G.; Metzelaar, M.J.; Wijngaard, P.L.J.; Nene, Vishvanath M.; Iams, K.P.; Roose, J.; Nyanjui, J.K.; Gobright, E.I.; Musoke, A.J.; Clevers, H.C. (1995)
Theileria parva, a tick-transmitted protozoan parasite related to Plasmodium spp., causes the disease East Coast fever, an acute and usually fatal lymphoproliferative disorder of cattle in Africa. Previous studies using sera from cattle that have survived infection identified a polymorphic immunodominant molecule (PIM) that is expressed by both the infective sporozoite stage of the parasite and the intracellular schizont. Here we show that mAb specific for the PIM Ag can inhibit sporozoite invasion of lymphocytes in vitro. A cDNA clone encoding the PIM Ag of the T. parva (Muguga) stock was obtained by using these mAb in a novel eukaryotic expression cloning system that allows isolation of cDNA encoding cytoplasmic or surface Ags. To establish the molecular basis of the polymorphism of PIM, the cDNA of the PIM Ag from a buffalo-derived T. parva stock was isolated and its sequence was compared with that of the cattle-derived Muguga PIM. The two cDNAs showed considerable identity in both the 5' and 3' regions, but there was substantial sequence divergence in the central regions. Several types of repeated sequences were identified in the variant regions. In the Muguga form of the molecule, there were five tandem repeats of the tetrapeptide, QPEP, that were shown, by transfection of a deleted version of the PIM gene, not to react with several anti-PIM mAbs. By isolating and sequencing the genomic version of the gene, we identified two small introns in the 3' region of the gene. Finally, we showed that polyclonal rat Abs against recombinant PIM neutralize sporozoite infectivity in vitro, suggesting that the PIM Ag should be evaluated for its capacity to immunize cattle against East Coast fever.